2007
DOI: 10.1007/s10641-007-9267-9
|View full text |Cite
|
Sign up to set email alerts
|

Nesting habitat use and partitioning of three sympatric ninespine sticklebacks (genus Pungitius): implications for reproductive isolation

Abstract: The nest site characteristics and distribution patterns of nests of three sympatric ninespine sticklebacks, the brackish-and fresh-water types and Pungitius tymensis, were investigated in the Shiomi River, eastern Hokkaido, Japan. In this river, most of the males of the brackish-water type were found to build their nests in the lower reach with higher salinity (mean 13.5%) and water temperature (mean 13.3°C), whereas the males of the freshwater type and P. tymensis built their nests in the upper reach with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…Second, introgression of mtDNA from P. pungitius into P. laevis might have occurred due to historical hybridization between them. Based on allozyme and mtDNA analyses, it has been shown that hybridization and mtDNA introgression often occur between different Pungitius species or different P. pungitius lineages in areas of sympatry in East Asia (Takahashi & Takata, ; Takahashi et al ., ; Tsuruta et al ., ). Given these two possible scenarios, further analyses of nuclear genomes are required to clarify the evolutionary process and mechanisms underlying the discrepant patterns of phenotypic and mtDNA divergence in the P. laevis lineage III.…”
Section: Discussionmentioning
confidence: 97%
“…Second, introgression of mtDNA from P. pungitius into P. laevis might have occurred due to historical hybridization between them. Based on allozyme and mtDNA analyses, it has been shown that hybridization and mtDNA introgression often occur between different Pungitius species or different P. pungitius lineages in areas of sympatry in East Asia (Takahashi & Takata, ; Takahashi et al ., ; Tsuruta et al ., ). Given these two possible scenarios, further analyses of nuclear genomes are required to clarify the evolutionary process and mechanisms underlying the discrepant patterns of phenotypic and mtDNA divergence in the P. laevis lineage III.…”
Section: Discussionmentioning
confidence: 97%
“…All of the three major subclades have a geographical distribution in the Far East. An interesting ecological and physiological feature in the species of the sinensisclade is that while P. pungitius is found in both freshwater and marine habitats, sinensis species are known to inhabit only freshwater environments, possibly because of their low salinity tolerance (Ishikawa et al, 2013;Takahashi & Goto, 2001;Tanaka & Shinbo, 1985;Tsuruta, Machida, & Goto, 2008). Likewise, their current distributions are thought to be largely associated with past geographical changes in this area (Takahashi & Goto, 2001).…”
Section: Biogeography Of Pungitius Sticklebacksmentioning
confidence: 99%
“…In eastern Hokkaido, for example, the brackish water type, the freshwater type and P. tymensis often inhabit the downstream, midstream and upstream of a single river, respectively, but their distributions often overlap. In those areas, the frequencies of hybrids are low, and reproductive isolation is achieved through a combination of eco-geographical isolation, ecological selection against migrants and hybrid male sterility Tsuruta et al, 2008;Ishikawa et al, 2013). In several areas along Omono River in Akita prefecture, the Omono type and the freshwater type are sympatric, but strong assortative mating maintains a low frequency of hybridization (Tsuruta et al, 2002).…”
Section: Ninespine Stickleback Species Complexmentioning
confidence: 99%